Prevalence and clinical association of gene mutations through multiplex mutation testing in patients with NSCLC: results from the ETOP Lungscape Project - Kerr, Keith M.; Dafni, U.; Schulze, K.; Thunnissen, E.; Bubendorf, L.; Hager, H.; Finn, S.; Biernat, W.; Vliegen, L.; Losa, J. H.; Marchetti, A.; Cheney, R.; et al. (Annals of oncology, 2018)
Reported prevalence of driver gene mutations in non-small-cell lung cancer (NSCLC) is highly variable and clinical correlations are emerging. Using NSCLC biomaterial and clinical data from the European Thoracic Oncology Platform Lungscape iBiobank, we explore the epidemiology of mutations and association to clinicopathologic features and patient outcome (relapse-free survival, time-to-relapse, overall survival).